Empowerment of Women in the Making of Household Practices in Air Dingin Village Bukit Raya sub District Pekanbaru City - Jas, Jaspar; Bahar, Aswandi; Alvi, Ria Rizkia; Jas, Jaspar; Bahar, Aswandi; Alvi, Ria Rizkia (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to find out the profile of womens empowerment and how positive the empowerment of women in making household workshops in Air Dingin Village, Bukit Raya District, Pekanbaru City. This study uses a quantitative approach with descriptive analysis in the form of percentages. The method used in this research is survey method. The study was conducted in the UPPKS group of Air Dingin sub-district, Bukit Raya City Pekanbaru, as many as 30 people. Sampling in this study uses saturated sampling technique. The instrument used was a questionnaire / questionnaire. The results of the study showed that the profile of womens empowerment in the making of handicrafts in Air Dingin Village, Bukit Raya Sub-District, Pekanbaru City was considered good / positive. The results of data processing related to how positive the empowerment of women in making household workshops in Air Dingin Village, Bukit Raya District, Pekanbaru City, the results were classified as good / positive with a percentage of 72.3%. This means that the empowerment of women in making household crafts in Air Dingin Village, Bukit Raya Sub-District, Pekanbaru City, has been able to provide enormous benefits and contributions for mothers in increasing family income and increasing womens independence.